1874-75 Ark. Acts 156-57 - (:unkn) unknown (My University, 1875)
Prohibited the open or concealed carry of "any pistol of any kind whatever, or any dirk, butcher or Bowie knife, or sword or spear in a cane, brass or metal knucks, or razor, as a weapon."
Keywords: CARRY